Working Long Hours and Its Impact on Family Relations: Experiences of Employed Women in D.G. KHAN - Abbas, Aamir; Fatima, Dr. Kanez; Imran, Muhammad (University of Wah Journal of Social Sciences, 2019)
Long working hours affect the life of both men and women. But the impact of long working hours has been greater on the women as compared to men regarding their family relations. The aim of this study is to find out the impact of working long hours of employed women on family relations. A sample of 160 long hours working “employed” women of public and private sectors from the study areas of Tehsil Dera Ghazi Khan has been taken. To find out the impacts of long working hours of women on family relations we had applied linear regression, chi-square test and Cronch Bach’s alpha for reliability. Results of the present study concluded that situation of working long hours has a significant positive impact on the employed women family relations. Whereas the women working for long hours had a negative impact on children’s grooming and socialization because of lack of their care. Furthermore, the working long hours also had a negative impact on mutual understanding among spouses. Findings of the study concluded that “long working hour’s women” experience physical symptoms of stress such as fatigue, irritability, headaches and depression. Therefore, there is a need for protective laws to decrease employed women’s working hours, providing training about health safety measures, time management & nutrition education so that these employed women perform their work activities in a better way and play a significant role at their workplaces.